Mixed-methods approaches in health research in Nepal (Nepal Journal of Epidemiology, 2014)
Combining and integrating a mixture of qualitative and quantitative methods in one single study is widely used in health and social care research in high-income countries. This editorial adds a few words of advice to the novice mixed-methods researcher in Nepal.DOI: http://dx.doi.org/10.3126/nje.v4i5.11993 Nepal Journal of Epidemiology 2014; 4(5):415-16